Hubungan Burnout dengan Kinerja Perawat Pelaksana di Rumah Sakit GMIM Siloam Sonder - najoan, zefanya -; Pondaag , Ferlan; Adriani Natalia (Mapalus Nursing Science Journal, 2024)
Background: Physical or mental or emotional fatigue experienced by a nurse in an emotionally demanding situation is ad phenomenon depicting burnout. The long-term effects of burnout, when a nurse feels a general presence, the work environment will go to an inflexible level, when the situation is allowed to drag, will cause performanceto decline. Purpose: The study aims to find out burnout’s relationship with the performance of executive nurses at the GMIM Siloam Sonder hospital. Method: The study is a quantitave study with correlation analysis, to see if there is a link between variables with the cross sectional study approach. The sample in this study is the managing nurse of 53 people who were procured using a total sampling. Research instruments using an MBI questionnaire (Maslach Burnout Inventory) and the 2017 formal performance questionnaire was then analysed using a spearmen test. Result: Based on research acquired value p = 0,002 (a<0.05) so it suggests a link between burnout and the performance of the executive nurse, with a coefficient correlation of 0,412, which means that a variable relationship is medium with a positive value and the therefore makes the two variables one way or another, Conclusion: From this research the heavier the burnout, the less the performance of the executive nurse will be.